Comparing the effects of different non-pharmacological traditional Chinese medicine therapies on cancer survivors: A Bayesian Network Meta-analysis - Shaowang Zhang; Yuanyin Li; Zhide Liang; Jiaxing Dai; Hong Huang; Huanghui Zhang; Bing Yang; Jinghui Wang; Dongxin Tang (Complementary Therapies in Medicine)
Objectives: Several studies have demonstrated the positive impact of non-pharmacological Traditional Chinese Medicine (TCM) therapies on pain, fatigue, sleep quality, and quality of life in cancer survivors. However, no research has compared the effectiveness of these therapies. This study aims to compare various interventions and identify the most effective non-pharmacological TCM therapies to provide evidence-based recommendations for cancer survivors. Methods: A systematic search was conducted in PubMed, Embase, Web of Science, CNKI, and Wanfang Data. RCTs investigating the effects of Taichi, Qigong, acupuncture, acupressure, TCM emotional therapy, and mixed therapies as interventions for cancer survivors were screened was conducted. Data from the creation of the database to February 2025 were included. Two independent reviewers evaluated the study quality. A Bayesian Network Meta-analysis was conducted to carry out a random effects model. Results: Seventy-one RCTs involving 6473 patients were included in the analysis. Network meta-analysis showed significance for all five intervention therapies in pain control in cancer patients. The best efficacy was observed for acupressure (SMD=-1.1 [-1.55, −0.66]) and Taichi/Qigong (SMD=-1.08[-1.64, −0.53]), followed by TCM emotional therapy (SMD=-0.93 [-1.42, −0.44]) and acupuncture (SMD=-0.54 [-0.93, −0.15]), with the latter showing comparatively lower efficacy. None of the interventions demonstrated superior efficacy in improving fatigue compared to the control group. Mixed therapies (SMD=-1.36[-2.56, −0.28]) demonstrated the greatest effect in improving sleep quality. Taichi/Qigong (SMD=1.87 [0.96, 2.83]) demonstrated certain advantages in improving quality of life. However, acupuncture and TCM emotional therapy had no significant effect on sleep quality or overall quality of life. Conclusion: The evidence from this study suggests that acupressure and Taichi/Qigong are recommended as the most effective therapies for pain relief and quality of life improvement, respectively. The efficacy of these therapies for fatigue remains inconclusive. However, due to the limited number of included studies and the high risk of bias, these results should be interpreted with caution. Future studies should include more rigorously designed high-quality randomized controlled trials to confirm their long-term efficacy and safety. Registration: PROSPERO CRD42024601976